Fiscal Incentives and Financial Performance in Bonded Zone Companies: Insentif Fiskal dan Kinerja Keuangan Perusahaan di Kawasan Berikat - Pradianingsih, Rini; Setiyono, Wisnu Panggah; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: (General Background) Fiscal incentives such as bonded zone facilities have become key instruments for enhancing industrial competitiveness and export growth in Indonesia. (Specific Background) Despite their potential benefits, not all companies have successfully optimized customs and tax policies to improve financial performance. (Knowledge Gap) Previous studies mostly focused on export performance, leaving a gap in understanding their impact on profitability and capital structure. (Aims) This study examines how Customs Policy and Tax Restitution affect profitability (ROA) and capital structure (DER) among bonded zone companies listed on the Indonesia Stock Exchange from 2022–2024. (Results) Using multiple linear regression, results reveal that both Customs Policy and Tax Restitution significantly increase profitability and reduce leverage. (Novelty) This study provides new evidence on how fiscal policy effectiveness strengthens internal financing and financial stability. (Implications) The findings guide policymakers in improving fiscal incentive implementation and encourage firms to optimize internal cash management for sustainable financial growth. Highlights:• Fiscal incentives strengthen profitability and reduce leverage.• Customs Policy improves efficiency and operational cash flow.• Tax Restitution enhances liquidity and internal funding capacity. Keywords: Customs Policy, Tax Restitution, Profitability, Capital Structure, Bonded Zone